The role of social security in social progress in Vietnam - Tri, Nguyen Minh; Hau, Dao Tuan; Duyen, Nguyen Thi Thuy (Linguistics and Culture Review, 2021)
In the process of international integration, the State of Vietnam has always determined that implementing social security is both a goal and a driving force for sustainable development, maintaining socio-political stability. Over the years, Vietnam’s social security has contributed to building a people-centered economy in Vietnam. Although the implementation of social security in Vietnam has achieved certain results with social progress, there are still some limitations that need to be overcome in the coming time to continue to improve social security towards a just and progressive society. The article analyzes the current situation (results and limitations) of the role of social security in social progress in Vietnam in the process of international integration; thereby contributing to providing more scientific bases for the decisions of the Government of Vietnam to improve the social security system to ensure social progress nowadays.